Biyaya ng lupa - Rosal, Rosa; Santos, Tony; Salvador, Leroy
"A young married couple, Maria and Jose (Rosa Rosal and Tony Santos) start life together creating a lanzones orchard in the countryside. They have four children - Miguel (Leroy Salvador), Arturo (Carlos Padilla Jr), Angelita (Marita Zobel), and Lito (Danilo Jurado). The eldest, Miguel, is a deaf-mute. Life is good to them and the children grow up and bring joy to the community. But trouble enters their lives when Jose makes an enemy of Bruno (Joseph de Cordova). Bruno, a widower, is much feared in the village, for it is rumored that he caused the death of his wife. And yet he wants to remarry and is courting Choleng (Mila Ocampo), Jose's niece. But Choleng avoids Bruno and one day, in trying to get away from him, she slips and falls off a cliff and dies. The village is outraged and Bruno hides in the mountains. There, he plots his revenge on the village, particularly on Jose's family".--https://www.imdb.com/title/tt0159283/?ref_=fn_al_tt_1